Comparison of Minimally Invasive Loop Drainage and Standard Incision and Drainage of Cutaneous Abscesses in Children Presenting to a Pediatric Emergency Department: A Prospective, Randomized, Noninferiority Trial. Issue 10 (October 2021) - Rencher, Logan; Whitaker, Winnie; Schechter-Perkins, Elissa; Wilkinson, Matthew
Abstract : Objective: This study aimed to determine whether the treatment of skin abscesses with vessel loop drainage is noninferior to standard incision and drainage (I&D) regarding treatment failure in pediatric patients in the emergency department (ED). Methods: This study was a prospective, randomized controlled trial in a pediatric ED of an urban tertiary pediatric hospital. Patients with a skin abscess were enrolled. Subjects were assigned to the control arm of I&D or the study arm of vessel loop drainage. Study end points (failure rates, satisfaction scores, wound appearance, visit frequency) were assessed before discharge from the ED, at 24- to 48-hour follow-up, and at 14-day follow-up. Treatment failure was declared if the abscess required reinstrumentation or admission for intravenous antibiotics for systemic illness within 14 days. Results: From August 2014 to October 2015, 81 patients completed this study. Treatment failure was observed in 3 subjects of each arm (7.3% loop vs 7.5% standard; risk difference, 0.2%; 95% confidence interval, −11.2% to 11.6%). Parent satisfaction rates with wound appearance at day 14 were similar (86.1% loop vs 88.2% standard were at least satisfied). Median cosmetic scores were similar at day 14 (6 [interquartile range IQR, 5–6] loop vs 6 [IQR, 5–6] standard, where 6 was optimal). Follow-up visit frequency was similar (2 [IQR, 2–3] loop vs 2 [IQR, 2–2.5] standard). Conclusions: Abscess drainage with a vessel loop in the pediatric ED results in failure rates noninferior to those of the standard I&D. Satisfaction and cosmetic scores are favorable in both groups.